THE USE OF VIRTUAL REALITY AND ITS IMPACTION REGARDING LEARNING ATTITUDE AMONG YOUNG ADULTS IN BANGI, SELANGOR, MALAYSIA - Aris Abdul Rahman; Khairudin Murad; Wardatul Hayat Adnan, (INTERNATIONAL JOURNAL OF EDUCATION, PSYCHOLOGY AND COUNSELLING (IJEPC), 2024)
Virtual Reality (VR) technology is a computer-based simulation system designed to create novel learning experiences within a virtual realm. VR establishes a simulated environment that has significant impact one's attitude toward learning. This new environment enables interaction with three-dimensional, dynamic views, thereby influencing physical learning behaviour. Virtual reality is a crucial component of the innovation process, facilitating real-time interaction within simulations and representing cutting-edge technology for enhanced comprehension of products. In contrast, traditional learning methods tend to be monotonous, whereas current educational approaches prioritise interactivity, saving time, fostering positive learning attitudes among young individuals, and enabling learning at any location and time. The primary objective of this study is to investigate the acceptance and utilisation of virtual reality among young adults and its effect on learning attitudes. One of the notable advancements in VR technology is its integration into educational institutions, with universities and schools emphasising alternative learning methods. This observation highlights the significance of embracing VR in a world increasingly focused on digitalisation. The study employs a quantitative methodology, utilising face-to-face surveys involving questionnaire distribution to a sample of 200 young adults within the Bangi, Selangor, Malaysia. The research findings reveal that Virtual Reality Hedonic Motivation plays a significant role in shaping the Behavioural Intention to use virtual learning (as indicated by a Pearson correlation of r=.726 and Regression R2 = .527). This result indicates that, VR is accepted as an alternative learning method, especially within the context of Malaysia, where online digitalisation is gaining prominence within the education sector. This discussion on existing literature provide valuable insights for future researchers seeking to enhance the learning attitudes of young adults through the integration of VR technology.